2019
DOI: 10.1002/aet2.10326
|View full text |Cite
|
Sign up to set email alerts
|

Resident Clinical Experience in the Emergency Department: Patient Encounters by Postgraduate Year

Abstract: Background: During emergency medicine (EM) training, residents are exposed to a wide spectrum of patient complaints. We sought to determine how resident clinical experience changes based on training level in relation to the patient acuity levels, chief complaints, and dispositions. Methods:We performed a retrospective chart review of patients seen at a safety-net, academic hospital in Los Angeles from July 1, 2015, to June 30, 2016. Resident postgraduate year (PGY) level and specialty, patient acuity (based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…This study capitalizes on the availability of clinical information associated with the increased reliance on electronic medical records (EMRs). As demonstrated by Douglass et al . this type of approach can inform current and future curricular interventions based on the diversity that exists in the current training environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study capitalizes on the availability of clinical information associated with the increased reliance on electronic medical records (EMRs). As demonstrated by Douglass et al . this type of approach can inform current and future curricular interventions based on the diversity that exists in the current training environment.…”
Section: Discussionmentioning
confidence: 99%
“…The ABEM Model provides the structure and guidance for current EM training, so it is reassuring that all categories were represented, albeit some in lower volumes. Several prior studies have identified challenges with tracking the EM resident clinical experience and assuring adequate clinical exposure . New approaches are required to assess the training environment and the current training standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of patients seen by residents in Taipei and Keelung branches Pre-epidemic period Epidemic period P valueDiscussionThe objective of EM residency training is to enhance residents' knowledge and breadth of clinical experience. Speci cally, the primary goal of EM residency training programs is to ensure that residents gain the required clinical experience to master the knowledge and clinical skills necessary to practice EM (12). Case exposure based on seeing a variety of patients with varying acuity levels, chief complaints, and…”
mentioning
confidence: 99%
“…Characteristics of patients seen by residents in Linkou general hospital Pre-epidemic period Epidemic period P valueDiscussionThe objective of EM residency training is to enhance residents' knowledge and breadth of clinical experience. Speci cally, the primary goal of EM residency training programs is to ensure that residents gain the required clinical experience to master the knowledge and clinical skills necessary to practice EM (12). Case exposure based on seeing a variety of patients with varying acuity levels, chief complaints, and diagnoses is crucial for the development of comprehensive experience (13)(14)(15).…”
mentioning
confidence: 99%